The Influence of Job Stress and Work Motivation on Employee Performance at PT. KGS - Aulia, Nisa; Sudinta, Heru; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study examines the importance of employee performance as a key factor in corporate success, particularly in manufacturing companies. At PT KGS, high workloads, declining attendance discipline, lack of work motivation, and production results that repeatedly fall short of targets were observed. These conditions have the potential to cause work stress and reduce employee performance. Therefore, this study aims to determine the effect of work stress and work motivation on employee performance at PT KGS, both partially and simultaneously.This study used a quantitative approach with an associative approach and a survey method. The population was all 43 PT KGS employees, with a sample of 30 respondents determined using the Slovin formula with a 10% margin of error. Data were obtained through a closed-ended questionnaire based on a Likert scale (1–5) measuring work stress (X1), work motivation (X2), and employee performance (Y). Data processing was performed using SPSS version 30 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests (partial), F-tests (simultaneous), and coefficients of determination.The research results indicate that work stress and work motivation play a role in employee performance. Partially, work stress impacts employee performance because high work pressure can reduce concentration, cause physical and emotional fatigue, and impact productivity. Meanwhile, work motivation also influences performance because high work drive can increase enthusiasm, responsibility, and effectiveness at work. Simultaneously, work stress and work motivation jointly influence employee performance at PT KGS. Therefore, the company needs to pay attention to managing work stress and increasing employee motivation to maintain optimal performance and achieve production targets.